REPRODUCTION AND LARVAL REARING OF SANDFISH (Holothuria scabra) - Sembiring, Sari Budi Moria; Wibawa, Gigih Setia; Giri, I Nyoman Adiasmara; Hutapea, Jhon Harianto; Haryanti, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2018)
The natural stock of sea cucumber Holothuria scabra (known as sandfish) has been declining in both population and size, making it difficult to collect broodstock and juvenile sandfishes for aquaculture. This research aims to evaluate the reproduction of domesticated broodstock (F-1) and performance of the juveniles (F-2). Broodstock were reared in two rectangular concrete tanks with a dimension of 190 x 290 x 70 cm3. There were 12 individuals (7 males and 5 females) of broodstock (F-1) with total length and mean body weight of 12.0 ± 1.21 cm and 122.6 ± 32.37 g, respectively. Six broodstock were put in each tank and fed with compressed benthos at 4% biomass daily in the afternoon. During our experiment, domesticated sandfish broodstock successfully spawned twice. The first spawning (occurred in January 2017) had one female spawned that released 1,350,000 eggs with a hatching rate of 57.4%. Another broodstock spawned in April 2017 and produced 3,280,000 eggs with a hatching rate of 78.66%. The growth performance of 170 days-old juveniles (F-2) shows a total length of 5.66 ± 0.90 cm and a mean body weight of 10.08 ± 2.07 g. The survival rates are 5.19% and 8.68% for juveniles spawned in January and April, respectively. We conclude by showing that sandfish could be domesticated to produce seeds for further aquaculture development.